Association between abdominal aortic aneurysms and alcohol-related diseases. Issue 44 (30th October 2020) - Li, Ling-Yuan; Chien, Wu-Chien; Wang, Jen-Chun; Tzeng, Nian-Sheng; Chung, Chi-Hsiang; Lin, Chih-Yuan; Tsai, Shih-Hung
Abstract : Abstract: Heterogeneous associations exist between alcohol consumption and the initial presentation of cardiovascular diseases (CVDs). Studies regarding the association between abdominal aortic aneurysms (AAAs) and alcohol consumption are still limited and controversial. We hypothesize that patients with alcohol-related diseases are susceptible to AAA formation due to the presence of overlapping epidemiological factors and molecular mechanisms. We aimed to use a nationwide population-based retrospective cohort study to evaluate the association between alcohol-related diseases and AAA. The data were extracted from the National Health Insurance Research Database (NHIRD) in Taiwan. The study outcome assessed was the cumulative incidence of AAA in patients with alcohol-related diseases during a 14-year follow-up period. Our study included 22, 878 patients who had alcohol-related diseases; these patients with alcohol-related diseases had a significantly higher cumulative risk of developing AAA 5 years after the index date than did the 91, 512 patients without alcohol-related diseases. Patients with alcohol-related diseases also exhibited a significantly increased incidence of AAA compared with the incidence among patients without alcohol-related diseases, according to Cox regression analysis and Fine & Gray's competing risk model (adjusted hazard ratio = 2.379, 95% confidence interval = 1.653 -3.424, P  < .001). In addition, male gender, older age, and chronic kidney disease were also associated with an increased risk of developing AAA. An interaction model showed that males with alcohol-related diseases had a 10.4-fold higher risk of AAA than did females without alcohol-related diseases. We observed an association between alcohol-related diseases and AAA even after adjusting for several comorbidities and medications in a nationwide population database.